Pendeteksian Anomali Trafik Jaringan Menggunakan Metode Decision Tree - Muhammad Iqbal Manalu; Hutabarat, Fatur Padilla (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
With the increasing penetration of computer networks connected to the internet, the risk of network intrusion is also on the rise. Such intrusions attempt to bypass network security mechanisms. One way to detect intrusions is by analyzing network traffic activities. However, manually analyzing all network data can be cumbersome and time-consuming. You can use decision trees to classify network events based on specific attributes. This enables the creation of rules that can detect anomalies in network traffic patterns. We can develop these rules by mapping network events to unique segments within the decision tree. Constructing rules based on the sequence of segments from the decision tree allows for the identification of intrusion indicators, aiding in detecting intrusion attempts in the network. This approach provides a more efficient means for network analysts to identify abnormal network traffic activities without the need for manual inspection of every data point. Thus, the use of decision trees enhances the capability to detect network intrusions, safeguarding computer networks from increasingly complex and diverse cyber threats. This represents a crucial step in fortifying our digital infrastructure's security.